DISTRIBUTION OF MONOGONONT ROTIFERS, Branchionus spp IN NORTH SULAWESI - Rimper, Joice; Kaswadji, Richardus; Widigdo, Bambang; Sugiri, Nawangsari; Rumengan, Inneke (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
In order to characterize the distribution pattern of rotifers Brachionus spp. in North Sulawesi, sample collections have been conducted at four locations, two at east coast and other two at west coast of North Sulawesi peninsula, which are connected to Maluku and Sulawesi Seas, respectively. At each location, a 40 p.m mesh size plankton net with a 0.3 m opening diameter was horizontally towed at three sites to represent coastal water, estuary and brachkiswater pond. Sampling periods were in January and August 2005 to represent west monsoon and east monsoon, respectively. Each sampling was performed twice a day during high and low tide. Some environmental factors were also measured in situ during the sampling. Three species of Brachionus were found during the survey, Brachionus rotundiformis, B. caudatus and B. quadridentatus. Their abundances were significantly different, both between locations and sampling sites. However, among the similar habitat such as between Manembo-nembo and Minanga brachkishwater ponds, B. rotundiforms abundance was not significantly different. This species was the most abundant compared to the other two species, in average 1984,4 ind/m3, while the other species was as low as 26,1 ind/m3 and 212,9 ind/m3 for B. caudatus and B. quadridentatus, respectively. The abundance of rotifers in northern areas connected to Molluccas Sea is higher compared to those in the southern areas connected to Sulawesi Sea. Distribution of B. caudatus is very similar to those of B. rotundiformis, while B. quadridentatus appears to have its specific pattern. Results of this study suggest that the abundance and species composition of the rotifers reflect trophic status of the aquatic ecosystem in the area. It is still awaiting future studies to elaborate the impacts of the trophic gradients in horizontal distribution of rotifers. Therefore, it is necessary to conduct a long term monitoring with emphasis on the structure of rotifer assemblages in a variety of sites subjected to environmental perturbations, including anthropogenic contaminant inputs.